2011
DOI: 10.1590/s1807-59322011001200017
|View full text |Cite
|
Sign up to set email alerts
|

Moderate exercise training promotes adaptations in coronary blood flow and adenosine production in normotensive rats

Abstract: OBJECTIVES:Aerobic exercise training prevents cardiovascular risks. Regular exercise promotes functional and structural adaptations that are associated with several cardiovascular benefits. The aim of this study is to investigate the effects of swimming training on coronary blood flow, adenosine production and cardiac capillaries in normotensive rats.METHODS:Wistar rats were randomly divided into two groups: control (C) and trained (T). An exercise protocol was performed for 10 weeks and 60 min/day with a tail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 36 publications
1
18
0
6
Order By: Relevance
“…Many cross-sectional studies have demonstrated that trained endurance athletes present skeletal muscle oxidative enzyme activities that are much greater than those of their sedentary counterparts [10, 12, 22]. These increases in oxidative capacity are associated with increases in skeletal muscle mitochondrial content via mitochondrial biogenesis [23] and are consistent with the previously shown relationship between capillarity and mitochondrial content [9, 24, 25].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Many cross-sectional studies have demonstrated that trained endurance athletes present skeletal muscle oxidative enzyme activities that are much greater than those of their sedentary counterparts [10, 12, 22]. These increases in oxidative capacity are associated with increases in skeletal muscle mitochondrial content via mitochondrial biogenesis [23] and are consistent with the previously shown relationship between capillarity and mitochondrial content [9, 24, 25].…”
Section: Discussionsupporting
confidence: 64%
“…Capillary growth in skeletal and cardiac muscle is a complex process mediated by several metabolic alterations occurring during muscle activity and factors linked to increased shear stress induced by blood flow and passive stretch of the vascular smooth muscle tissue [5, 11, 12]. …”
Section: Introductionmentioning
confidence: 99%
“…These data indicate that baroreflex dysfunction associated with changes in the renin angiotensin system may be predictive factors of left ventricular hypertrophy and cardiac failure. Roque et al [50] investigated the effects of swimming training on coronary blood flow, adenosine production and cardiac capillaries in normotensive rats and found that swimming training increases coronary blood flow, number of cardiac capillaries, and adenine nucleotide hydrolysis. Increased adenosine production may be an important contributor to the enhanced coronary blood flow and angiogenesis that were observed in the exercise-trained rats; collectively, these results suggest improved myocardial perfusion.…”
Section: Kk and Rocha E Silva M -Cardiology In Brazilian Scientific Joumentioning
confidence: 99%
“…Trabalhos têm mostrado que diversas situações como idade, condições clíni-cas e o próprio treinamento físico induzem angiogênese 28 . Roque et al 29 verificaram aumento do número de capilares de músculos papilares do coração de ratos submetidos ao treinamento de natação por 10 semanas. Leosco et al 30 verificaram que o treinamento em esteira por 10 semanas induziu angiogênese coronária em ratos com insuficiência cardíaca.…”
Section: Discussionunclassified